HUNTING for EST and biological significance breakthroughs in M. rosenbergii, the Malaysian giant freshwater prawns - Bhassu, Subha; Zhang, Guojie; Othman, Rofina Yasmin; Kwong, Qi Bin; Jaafar, Azwan; Easwvaran, Sarasvathi (Elsevier, 2010)
[no abstract available]